Prevalence of Iron-Deficiency Anemia and Consumption of Iron in Hospitalized Children - Panato, Cristyane da Silva Siqueira (2011)
Iron-deficiency anemia is a lack of iron and hemoglobin decrease in the body. It is the highest extensive nutritional deficiency worldwide. Current analysis determines the relationship between prevalence of iron-deficiency anemia and iron consumption in hospitalized children. Descriptive research employs the clinical charts of 41 children hospitalized from August to October 2007 in a government hospital in Maringá PR Brazil. Iron-deficiency anemia was characterized by hemoglobin rate